Islamic Philanthropy in the Indonesian Sharia Capital Market: Filantropi Islam di Pasar Modal Syariah Indonesia - Yusuf Zaini Aprizal; Iva Faizah; Anas Malik (El-Qist: Journal of Islamic Economics and Business (JIEB), 2022)
Abstract: Islamic philanthropy is a practice of generosity in Islamic teachings in the form of acts of ta'āwun to fellow Muslims. This can be carried out in the form of zakāh, infāq, alms, and endowments. Philanthropic activity is worship in Islam which is not only a reflection of the relationship between a Servant (worship) with Allah almighty alone but is closely related to mu‘āmalah or human relations, or what is commonly referred to as ḥablu min Allāh and ḥablu min al-Nās. So far, the practice of Islamic philanthropy in the Indonesian Sharī‘ah Capital Market (PMSI) has been carried out by several securities companies in collaboration with national zakāh institutions. This study aims to examine the development of Islamic philanthropy in the form of stock zakāh, stock donations, and stock waqf in the Indonesian Islamic capital market. The research method used is descriptive qualitative. The data used is secondary data, the authors obtained this data from the 2021 Islamic capital market development report. Islamic philanthropic features at PMSI itself have been provided by several securities companies, namely MNC Securities, BNI Securities, FAC Securities, HP Securities, Phillip Securities, Panin Securities, and Samuel Securities. During the 2021 period, the development of Islamic philanthropy at PMSI, both in terms of the number of philanthropic funds raised and investors carrying out philanthropic activities, grew very well. For zakāh stocks, the value of zakāh in the form of stocks grew 47.55%, and the number of investors who gave zakāh grew 161.54%, then infāq stocks, the value of infāq in the form of stocks grew 13.42%, and the number of investors who gave zakāh grew 14.74%, and for waqf stocks, the value of waqf in the form of stocks grew 8.7%, and the number of investors who gave waqf grew 28.40%. Keywords: Islamic Philanthropy, Capital Market Sharī‘ah , Zakāh, Waqf.   Abstrak: Filantropi Islam merupakan praktik kedermawanan dalam ajaran Islam, berupa perbuatan ta'āwun kepada sesama muslim, hal tersebut dapat dilaksanakan dalam bentuk zakat, infak, sedekah, dan wakaf (ZISWAF). Kegiatan filantropi merupakan ibadah dalam Islam yang bukan hanya cerminan hubungan antar seseorang hamba (ibadah) dengan Allah SWT. semata, melainkan erat kaitannya dengan mu‘āmalah atau hubungan sesama manusia, atau yang biasa disebut dengan ḥablu min Allāh dan ḥablu min al-Nās. Sejauh ini praktik filantropi Islam di Pasar Modal Syariah Indonesia (PMSI) telah dilakukan oleh beberapa perusahaan sekuritas yang berkejasama dengan lembaga zakat nasional. Penelitian ini bertujuan untuk mengkaji tentang perkembangan filantropi Islam berupa zakat saham, infak saham, dan wakaf saham yang ada di pasar modal syariah Indonesia. Metode penelitian yang digunakan adalah kualitatif deskriptif. Data yang digunakan merupakan data sekunder, penulis peroleh data tesebut dari laporan perkembangan pasar modal syariah 2021. Fitur filantropi Islam di PMSI sendiri telah disediakan oleh beberapa perusahaan sekuritas yaitu MNC Sekuritas, BNI Sekuritas, FAC Sekuritas, HP Sekuritas, Phillip Sekuritas, Panin Sekuritas, dan Samuel Sekuritas. Selama periode tahun 2021 perkembangan filantropi Islam di PMSI baik dari segi jumlah dana filantropi yang dihimpun maupun investor yang melakukan kegiatan filantropi tumbuh dengan sangat baik. Untuk zakat saham nilai zakat dalam bentuk saham tumbuh 47,55% dan jumlah investor yang berzakat tumbuh 161,54%, selanjutnya infak saham nilai infak dalam bentuk saham tumbuh 13,42% dan jumlah investor yang berinfak tumbuh 14,74%, dan untuk wakaf saham nilai wakaf dalam bentuk saham tumbuh 8,7% dan jumlah investor yang berwakaf tumbuh 28,40%. Keywords: Filantropi Islam, Pasar Modal Syariah, Zakat, Wakaf.